Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.physa.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of domain growth on spatial correlations

Abstract: Mathematical models describing cell movement and proliferation are important tools in developmental biology research. In this work we present methods to include the effects of domain growth on the evolution of spatial correlations between agent locations in a continuum approximation of a one-dimensional lattice-based model of cell motility and proliferation. This is important as the inclusion of spatial correlations in continuum models of cell motility and proliferation without domain growth has previously bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 40 publications
(140 reference statements)
0
15
0
Order By: Relevance
“…This approximation has been previously published [26], and reasonably implies that domain growth 'dilutes' the agent density [16] (we present analysis of the accuracy of this approximation in Section S2 of the supplementary information). Finally, we simplify Eq.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…This approximation has been previously published [26], and reasonably implies that domain growth 'dilutes' the agent density [16] (we present analysis of the accuracy of this approximation in Section S2 of the supplementary information). Finally, we simplify Eq.…”
mentioning
confidence: 61%
“…The approximation we employ in Eq. (6) in the main text has been previously published [16,17,26], and in Ross et al [16] its accuracy for a one-dimensional lattice-based model has been demonstrated. In terms of one-point density functions this approximation…”
Section: S2: Analysis Of Closure Approximationmentioning
confidence: 83%
See 3 more Smart Citations